2015
DOI: 10.1007/s00580-015-2163-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities, antioxidant properties and phytoconstituents of essential oil from sweet basil (Ocimum basilicum L.) leaves

Abstract: This study investigated the biological activities of essential oil from sweet basil leaves via its effect on α-amylase, α-glucosidase and angiotensin-I-converting enzyme (ACE) activities, inhibition of Fe 2+ and sodium nitroprusside (SNP)-induced lipid peroxidation in rats' pancreas and heart homogenates. The phytoconstituents of the oil were analysed using gas chromatography (GC). The essential oil exhibited a dose-dependent inhibition of α-amylase (IC 50 =3.21 mg/mL), α-glucosidase (IC 50 =3.06 mg/mL) and AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 40 publications
4
34
0
4
Order By: Relevance
“…Quercitrin and luteolin were the predominant flavonoid compounds found in fluted pumpkin seed, this could contribute to its ACE inhibitory properties and studies have shown that flavonoids are strong inhibitors of ACE (Guerrero et al, ; Shodehinde et al, ). This finding is consistent with previous studies in which phenolic compounds from some tropical plants demonstrated ACE inhibitory properties (Ademiluyi & Oboh, ; Ademiluyi, Oyeleye, & Oboh, ; Akomolafe et al, ).…”
Section: Resultssupporting
confidence: 93%
“…Quercitrin and luteolin were the predominant flavonoid compounds found in fluted pumpkin seed, this could contribute to its ACE inhibitory properties and studies have shown that flavonoids are strong inhibitors of ACE (Guerrero et al, ; Shodehinde et al, ). This finding is consistent with previous studies in which phenolic compounds from some tropical plants demonstrated ACE inhibitory properties (Ademiluyi & Oboh, ; Ademiluyi, Oyeleye, & Oboh, ; Akomolafe et al, ).…”
Section: Resultssupporting
confidence: 93%
“…The inhibition of ACE activity in this study could be a function of interaction between the phenolics in the peels with disulphide bridge of the enzyme and/or chelation of zinc atom within the active site of the enzyme (John and Schmieder 2003;Ademiluyi et al 2015). This is in line with our previous studies that phenolic-rich extracts from some plant inhibited ACE activity Ademiluyi et al 2015;Akomolafe et al, 2016), Moreover, flavonoids such as rutin, quercetin and quercitrin which are dominant in UPP have been reported to be potent inhibitors of ACE activity (Guerrero et al 2012;Shodehinde et al 2016), and could be responsible for the higher inhibitory effect observed by UPP.…”
Section: Discussionmentioning
confidence: 88%
“…The reaction between superoxide and NO forms a highly toxic radical such as peroxynitrite, which is capable of reducing the available NO required for penile erection (Khan et al 2001;Agarwal et al 2006). The use of antioxidants has been reported to ameliorate oxidative stress via scavenging of free radicals and chelation of transition metals (Adefegha et al 2015;Ademiluyi et al 2015). So far, polyphenols which are abundant in plant-based human diet such as fruits and vegetables have been reported to be efficient in the management of ED and other related diseases such as hypertension with little or no side effects (Ferreira et al 2006;Oboh et al 2015;Akomolafe et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The control experiment was performed without the test sample. The percentage ACE inhibition was subsequently calculated (Ademiluyi, Oyeleye, & Oboh, ).…”
Section: Methodsmentioning
confidence: 99%